Pengaruh Citra Merek Dan Kesadaran Merek Terhadap Ekuitas Merek Cinema XXI - Nilsen Wiljaya; Richard Andrew (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
In the intense competition in the entertainment industry, brand image and brand awareness are key elements that can influence brand equity. This research aims to identify and analyze the influence of brand image and brand awareness on the brand equity of Cinema XXI in Jakarta. The quantitative method was used by taking a sample of 100 respondents who were regular visitors to Cinema XXI. Data was collected through questionnaires and analyzed using SMART-PLS and SPSS. The research results show that brand image has a significant influence on brand equity, confirming that a strong positive image can increase brand value. Brand awareness also has a positive impact on brand equity, indicating that a high level of recognition strengthens the brand's position in the market. These findings provide important insights for Cinema XXI managers to develop effective strategies in strengthening their image and increasing brand awareness, which will ultimately strengthen their brand equity in the competitive entertainment industry.